Gestão de cadeia de suprimentos e o impacto no desempenho operacional das empresas: um estudo empírico no Brasil - Miguel, Priscila Laczynski de Souza (2008)
Despite the recent increase of publications on the subject, the area of supply chain management (SCM) still faces two important challenges: its theoretical development is still in its early stages and it lacks empirical evidence of its benefits. There is still a need to achieve consensus on its definition and its constructs (BURGUESS, SINGH; KOROGLU, 2006; CHEN; PAULRAJ, 2004, COUSINS; LAWSON; SQUIRE, 2006; HARLAND et al., 2006) and most of the published studies on the subject do not explain it on a theoretical perspective (BURGUESS, SINGH; KOROGLU, 2006; KETCHEN; HULT, 2007), representing an additional difficulty for practitioners and academics to verify the effectiveness of the strategy on the performance of companies. Besides that, the results of empirical studies are not conclusive due to research design differences. Based on the transaction cost theory, resource based view and relational view and in the recent empirical papers review, this study presents an integrative conceptual model of antecedents and consequences of SCM. The constructs are operationalized based on extensive review of empirical literature on the subject in order to increase the consistency of the scales of measurement and provide a tool for future research. Using structural equation model, alternative measurement models for the antecedents of SCM and operational performance are tested based on a sample of 107 companies in Brazil. The results do not show that there is a multidimensional construct responsible for the SCM implementation, but suggest the existence of independent and correlated dimensions, such as benevolence, credibility, top management support and internal relationships. A comparison of the models of operational performance provides evidence that this construct can be treated as a latent variable of second order, but can also be analyzed in its dimensions of cost, quality, flexibility and time. Additionally we empirically tested a number of hypothesized relationships between SCM antecedents, SCM and operational performance. The results do not support the mentioned dimensions as antecedents of SCM, but there is evidence of the impact of supply chain management on operational performance and its various dimensions.